ALL-REZ BFM – The Consecutive Trials for Children with Relapsed Acute Lymphoblastic Leukemia - Henze, G.; Stackelberg, A. v.; Eckert, C. (Klinische Pädiatrie, 2013)
The BFM studies for relapsed childhood acute lymphoblastic leukemia (ALL) were started in 1983, at a time when cure rates for ALL were still lower and the number of children with ALL relapse equaled about the number of children with newly diagnosed neuroblastoma. Today, relapses have become relatively rare events in ALL although, because of the frequency of ALL, they are still a significant cause of death in children and adolescents. With currently used treatment modalities, cure rates of about 50% after relapse can be achieved, and, together with the improved results of front-line therapy, the survival rate of childhood ALL is now about 90%. Most children with extramedullary and late bone marrow (BM) relapses achieve a second CR; remission rates in patients with high-risk features, however, remain still unsatisfactory. With improved techniques allogeneic hematopoietic stem cell transplant (HSCT) has become a relatively safe treatment but is not necessary for all patients as postremission therapy. HSCT is not required in children with isolated extramedullary and late BM relapses with rapid response to induction therapy measured by molecular techniques (minimal residual disease, MRD) but absolutely indicated in patients with early BM relapses and systemic relapses of T-cell ALL. For patients with insufficient response innovative therapies such as small molecules or targeted immunological or pharmacological approaches are urgently required. Efforts have to be made, therefore, in order to detect potential biological or molecular targets, which can be used for individualized, more effective and hopefully less toxic therapies in the future.
Keywords: Relapsed ALL; minimal residual disease; allogeneic stem cell transplantation; targeted therapy